Implementasi Algoritma Base64 Pada Transfer Data JSON Rekam Medis Puskesmas Kembangseri Menggunakan CURL - Ahmad Leo; Muhammad Husni Rifqo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
Puskesmas is one of the health facilities provided by the government for the community. As an agency engaged in the health sector, in managing medical record data, many use electronic medical records. In the process of sending and receiving data lately, JSON format data is often used because it has few resources compared to other data exchange formats and utilizes the CURL open source project as data transfer connectivity. However, in the process of sending data, there have not been many efforts to secure the data. This is very unfortunate in the midst of many developments in data security methods that are not used so as to cause losses for information owners. Data security methods can be applied as a preventive effort to minimize the risk of data leakage incidents. The system development method used is the prototype development method, the algorithm used for the security method is Base64 and for the data object in this study is a JSON data format of string type. After carrying out this research and passing the whitebox testing process, it was concluded that the Base64 algorithm can be implemented in JSON format of string type.